POLA ASUH ORANG TUA DEMOKRATIS, EFIKASI-DIRI DAN KREATIVITAS REMAJA - Kasiati Kasiati; Niken Titi Pratitis Titi Pratitis; Muhammad Farid (University of Merdeka Malang, 2012)
Abstract Research for studies both simultaneous or partial correlations of democratic parenting and self-efficacy to creativity. Subject are 123 mid adolescence (60 boys and 63 girls), ages from 16 to 18 years old. Data taken from scales of C.O.R.E for creativity, P.A.O.D. for democratic parenting and ED-G for self-efficacy. Result of simultaneous test it R = 0,384, F = 10,349, p = 0,000 (p 0,05). Democratic parenting and self-efficacy simultaneously and significant would have predicting creativity. R2 = 0,147 refer that 14,7% varians proportion on creativity would hava explained from democratic parenting and self-efficacy, othre for 85,3% could explained from other factors that not self-efficacy. Constant of 146,671 is score of creativity if no democratic parenting and self-efficacy. Result of partial test of democratic parenting t = 0,420, p = 0,675 (p 0,05). Democratic parenting partially wasnt correlated with creativity. Result of partial test of self-efficacy t = 4,534, p = 0,000 (p 0,05). Self-efficacy partially was significantly positive correlated with creativity. The findings are disscussed in terms of their implications for mid adolescent context. Key words: creativity, democratic parenting, self-efficacy